Musical taste, employment, education, and global region. - North, Adrian; Davidson, J. (Wiley-Blackwell Publishing Ltd., 2013)
Sociologists have argued that musical taste should vary between social groups, but have not considered whether the effect extends beyond taste into uses of music and also emotional reactions to music. Moreover, previous research has ignored the culture in which participants are located. The present research employed a large sample from five post-industrial global regions and showed that musical taste differed between regions but not according to education and employment; and that there were three-way interactions between education, employment, and region in the uses to which participants put music and also their typical emotional reactions. In addition to providing partial support for existing sociological theory, the findings highlight the potential of culture as a variable in future quantitative research on taste.